Our habitual criminals - Falkiner, F. R. (Statistical and Social Inquiry Society of Ireland, 1882)
In seeking to take counsel with you here to-night on the grave problem our habitual criminals present, I have been most desirous not merely to iterate deplorings I have perhaps too often vainly made elsewhere, nor to suggest remedial action, which, plausible in itself, overlooks or underrates the difficulties which may render it impracticable. Those who even rightly contemplate existing evils from their own point are at times too prone to dictate changes, the carrying out of which lies outside their own sphere and responsibility, and then to brand as official obstruction the hesitation of the responsible departments to accept their methods.
Read before the Society, 25 April 1882
Keywords: Crime in Dublin; Habitual criminals; Persistent offenders; 314.15